Archives of Memory : A Soldier Recalls World War II - Hoffman, Alice M., 1929- (Book collections on Project MUSE., 2015)
""Tell me about the war""--These words launched a ten-year project in oral history by a husband-and-wife team. Howard Hoffman fought in World War II from Cassino to the Elbe as a mortar crewman and a forward observer. His war experiences are of intrinsic interest to readers who seek a foot soldier's view of those historic events. But the principal purpose of this study was to explore the bounds of memory, to gauge its accuracy and its stability over time, and to determine the effects of various efforts to enhance it. Alice Hoffman, a historian, initiated the study because she recognized the.